Синтагматична параметризація еквівалентів слова у парадигмі корпусної лінгвістики - Лучик, Алла; Остапова, Ірина (Видавництво Львівської політехніки, 2017)
This work offers possible ways to analyze syntagmatic properties of word equivalents, formed by a “preposition + noun” model. Linear sets in which word equivalents are functioning were discovered on the basis of texts from the Ukrainian National Linguistic Corpus. Grammar parameters of structural elements adjacent to studied units, which make up the syntagmas of 2–7 words, were described according to linguistics methodology. Integrated solution of assigned tasks should be preceded by syntagmatic splitting of Ukrainian National Linguistic Corpus texts, which is one of the aspects of its further development.
Keywords: Український національний лінгвістичний корпус; еквівалент слова; синтагма; синтагматичні відношення